Study of Maximum Oxygen Uptake (VO2 Max) Value in Indorunners Running Community of Malang and Surabaya City - Ummatun Khasanah; Maulana Fajar Wandhiro; Mochammad Guruh fitrianto (Indonesian Conditioning Coaches, 2024)
The aim of this research is, to determine the value of VO2 max which owned by the members of Indorunners community in Malang and Surabaya City. Besides, the high and low value of VO2 max assuredly depends on the variable of exercise, age, Body Mass Index (BMI), hospital sheet, occupation, and lifestyle of community members. This research is a descriptive quantitative research that uses survey method. The data retrieved using multistage fitness test and questionnaire. There are 50 subjects in this research; 36 men, and 14 women. The result of research shows that 50 community member can be categorized as; 3 members (6%) have excellent value of VO2 max, 14 members (28%) have good value of VO2 max, 21 members (42%) have enough or average value of VO2 max, 10 members (20%) have poor value of VO2 max, and 2 members (4%) have very poor value of VO2 max. Thus, the average value of VO2 max of running community Indorunners is fair. Moreover, the variable of age has dominant interrelatedness towards the value of VO2 max, according to both collation of the highest and lowest value of VO2 max with other components. While hospital sheet variable has the lowest interrelatedness towards the subject value of VO2 max. Therefore, the average value of VO2 max member of running community Indorunner in Malang and Surabaya city is fair. And the variable of age has the highest interrelatedness compare with other variables which influence the oxygen capacity value of VO2 max.